Australian art - Sayers, Andrew (Oxford : Oxford University Press, 2001)
Contents: ##1. Art and the Dreaming##2. The lines of empire 1788-1835##3. The pursuit of knowledge 1835-1870##4. Colonial art worlds 1851-1888##5. What should Australian artists paint? 1885-1900##6. Beautifying the objects of our daily life; art and decorative art 1890-1920##7. Order and transcendence; art between the wars 1919-1939##8. Aboriginal art and its reception 1934-1949##9. Art, myth, and society; the Australian avant garde 1939-1950##10. Icon and abstraction 1951-1968##11. Saying and seeing; contemporary art 1968-1999
boek